Máximas intensidades e índices de erosividade de chuvas para o Rio Grande do Norte - Santos, Wesley de Oliveira (2015)
Knowledge of extreme hydrological events is a requirement for drainage projects, waterproofing, dams, terraces and other engineering works, whether in urban or rural areas. To reduce the effects of floods, hydraulic works and those of erosion precess of contention for soil conservation, they are designed based on the maximum flow, observed statistically or based on rainfall-runoff models. For the development of equations IDF (intensity, duration and frequency), it is usually necessary to have a large rain gauge database, most of the time, are not accessible due to the lack of a continuous network monitoring or a few information available. Based on this, the objectives of this study were to determine the heavy rains equations (IDF curves) and erosivity indices EI30 and EI15 using daily rainfall data provided by EMPARN (Brazilian Agricultural Research Corporation) of (1964-2013) to municipalities the State of Rio Grande do Norte, through the use of daily rainfall disaggregation methodology. Daily rainfall data were organized in excel spreadsheet software in order to obtain the maximum annual daily rainfall and determine the erosive rainfall. Descriptive statistical analysis was performed with the aid of Excel software and R, version 2.12.1, beyond to verify the adherence precipitation data the probability distributions of Gumbel and Weibull through the Kolmogorov-Smirnov test at 5% significance. Rainfall posts of the municipalities were geo-referenced to the coordinate projection system (longitude and latitude) in degrees, Datum WGS 84, and the maps were drawn up with the aid of GIS software using the Kriging interpolation for spatial parameters of the equations IDF and erosivity indexes EI30 and EI15. There was a trend of better grip of rainfall data to the Gumbel distribution using the Kolmogorov-Smirnov test at 5% probability for the municipalities of Rio Grande do Norte. The spatial distribution of IDF function parameters and erosivity indexes showed the great variability of rainfall in the state of Rio Grande do Norte. The concentration of conservation practices should be distributed during the months of January, February, March and April, due to the occurrence of erosivity mayor this be four months